Education at School: A Process of Producing Whole Person - Stulpinas, Tomas (Acta Paedagogica Vilnensia, 1997)
The author reviews his research done on thc process of holistic (in Greek 'holos' mcans 'the whole') eclucation at school cluring the periocl 1963-1995. The concept implies the cclucation of the harmonious whole personality within the holistic peclagogical process. The author's research suggests a system of holistic eclucation at school. The subsystems are the integratecl processes of education and training. Their implementation is ensured by main interrelated elements, i. e„ the aims, foundations, content, methocls, and results of education. The elements of eclucation consist of components whose structure is further divided into details and microdetai!s. Holistic education at school is investigated as an integral theoretical system that gencralizes the empirical data of didactics, the theory of eJucation, aml practical experiences. A wicle theoretical perspective enablcs practitioncrs to so\ve separate educational problems in a more effective way. The main ideas of holistic education are being implernented at the Šiauliai Pedagogical Institute (Lithuania) in training and recertifying teachers.
Keywords: school; holistic education; training; upbringing; whole person